Management of Continous Postpartum Midwifery Care in Mrs. "S" at Sitti Khadijah 1 Mother and Child Hospital In 31 March s.d 25 May 2024 - Hidayah, Nurul; Firdayanti; Taherong, Ferawati; Al Kautzar, Anieq Mumthi’ah (Jurnal Midwifery, 2025)
Introduction The high number of maternal deaths during pregnancy or within 42 days after pregnancy termination, regardless of the duration and place of delivery, is caused by pregnancy or its management, leading to maternal mortality (MMR). In 2020, a total of 133 maternal deaths were reported, equivalent to 85.95 per 100,000 live births. These included 29 cases (22%) of maternal deaths during pregnancy, 36 cases (23%) during childbirth, and 77 cases (55%) during the postpartum period (Dinas Kesehatan, 2021). Method This study uses a case study approach, focusing on the Management of Continuous Postpartum Midwifery Care for Mrs. “S” at RSIA Sitti Khadijah 1 on March 31, 2024, in accordance with the midwife’s authority and needs, following the 7-step Varney management method and the SOAP approach. Results The case study involved an assessment through anamnesis and monitoring conducted four times within 42 days, followed by an additional visit after 42 days. During the midwifery care, early mobilization, uterine fundus massage, health education, breast care, breastfeeding techniques, on-demand breastfeeding, newborn care, and family planning counseling were provided. Conclusion The case study on Mrs. “S” with an episiotomy wound showed significant improvements. Postpartum monitoring at RSIA Sitti Khadijah 1 from March 31, 2024, to May 25, 2024, indicated that the postpartum mother had recovered from perineal sutures pain, experienced milk production, maintained normal vital signs, and showed no abnormalities during physical examinations